Effect of static and dynamic stretching on vertical jump performance in collegiate women volleyball players - Dalrymple, K. J.; Davis, S. E.; Dwyer, G. B.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the effect of stretching on peak jump height during a series of vertical jumps, specifically focusing on a) static stretching (SS), b) dynamic stretching (DS) and c) no stretching (NS) performed immediately before a series of countermovement vertical jumps (CMJ). Twelve female collegiate volleyball players (mean +/- SD; age 19.5 +/- 1.1 yr; height 1.71 +/- 0.06 m; mass 71.3 +/- 8.54 kg) volunteered for this study. Data collection lasted a total of 3 weeks, and each subject performed all 3 stretching protocols, 1 session per week, with 1 week between sessions. The order of the stretching protocols was randomized for each subject. During each testing session, all subjects performed a 5-minute light jog as a warm-up, followed by 8 minutes of 1 of the stretching protocols. One minute after the completion of each protocol, 5 maximal CMJ were performed on a force platform, with each jump separated by 1 minute of passive recovery. Jump heights were calculated by integrating the vertical force trace. There were no significant differences between the SS, DS, and NS conditions for any of the jumps (p > 0.05). Despite the lack of significant effects for the group, there were notable individual responses to each of the warm-up conditions. Practitioners should be aware of the individual responses of their athletes to different types of warm-up protocols before athletic performance and the possible impact of prescribing or eliminating certain exercises.